(G-INFASA) Totality of the Youth Movement in Treating The Economy during the Covid-19 Pandemic - Istikomah Istikomah; Siti Khayisatuzahro Nur; Abd. Rohman Fahruddin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The presence of Covid-19 has hit the community's economy. Banyuwangi as a regency that relies on the tourism sector as an economic driver has felt the impact. It resulted in the economic shock of the people of Banyuwangi. Muhammadiyah as one of the largest religious organizations in Indonesia plays an active role in community economic empowerment activities. Covid-19 also gave rise to a social response in the form of the Waste Infaq Movement (G-INFASA) from the Muhammadiyah Youth of Kalibaru Banyuwangi in the context of empowering the economy of the Kalibaru community. G-INFASA is a unique form of social response, there is a spirit of generosity and the spirit of developing Islamic philanthropy in achieving social welfare. The focus of research is the management of G-Infasa and the opportunities and challenges of G-INFASA in caring for the people's economy. The study aims to determine the role of the Muhammadiyah Kalibaru Banyuwangi Youth in empowering the Kalibaru community's economy through the development of Islamic philanthropy with waste as its asset. The method used is qualitative research with an Asset-Based Approach to Asset Based Community Development (ABCD), which in this case is waste. From the study, it was found that the management of G-INFASA in the ABCD (Asset Based Community Development) approach is supported by several aspects, namely related to community asset mapping and financial circulation analysis.